Seroprevalence of Chikungunya Virus Infection in an Urban Slum Population of Bangladesh: A Cross-Sectional Study (Journal of Current and Advance Medical Research, 2022)
Background: Chikungunya virus is common in Bangladesh.Objective: The aim of the study was to estimate the post-outbreak seroprevalence of chikungunya virus infection in a Bangladeshi urban slum population.Methodology: From April to May 2018, a cross-sectional study was conducted in Bauniabadh, an underprivileged slum area in Mirpur Thana (subdistrict), Dhaka, Bangladesh. Randomly selected residents of this area were interviewed and screened for chikungunya IgM and IgG antibodies in sera using the immunochromatographic process.Results: Randomly selected 403 residents were recruited of which 200 cases were male and 203 cases were female. Chikungunya seroprevalence was 4.7% cases with males being more vulnerable than females (6.5% vs. 3.0% ). People over the age of 60 years were found to be infected at a higher rate (7.2%) than people between the ages of 18 and 59 years (5.5%) and those in the pediatric age group (1%). During the outbreak, 22% of patients with joint pain and 17% with fever were diagnosed as having chikungunya. Conclusion Urban slum people, especially the elderly, are affected by chikungunya outbreak in Bangladesh characterized by fever and joint pain.Journal of Current and Advance Medical Research, January 2022;9(1):3-8